Model of Character Education as an Effort to Prevent Crime and Demoralization of Student in Makassar City - Rosmiati, Rosmiati; Syahid, Akhmad; Iqbal, Muhammad (Universitas Pendidikan Indonesia, 2022)
Abstract Development of a character education model as an effort to prevent crime and demoralization in children in State Elementary Schools. The research focuses on the development of learning tools and teaching materials at SDN Parangtambung 2 Makassar, Indonesia. The research method aused is qualitative methods. The research objective is to produce learning tools based on character education at SDN Parangtamung 2 Makassar. Then develop teaching materials for character education models at the SDN Parangtambung 2 Makassar, Indonesia. The result of this study is that the ccharacter eeducation model can be a means to prevent crime and violence in children at SDN Parangtambung 2 Makassar, Indonesia.Abstrak Model Pengembangan pendidikan karakter adalah usaha mencegah kejahatan dan demoralisasi pada anak di Sekolah Dasar Negeri (SDN) Parangtambung 2 Kota Makassar, Indonesia. Fokus penelitian ini adalah pengembagan perangkat pembelajaran dan pengembangan bahan ajar di SDN Parangtambung 2 di Kota Makassar, Adapun metode penelitian yang digunakan adalah metode kualitatif. Adapun Tujuan penelitian ini menghasilkan perangkat pembelajaran yang berbasis pendidikan karakter di SDN Parangtamung 2 Kota Makassar, Indonesia. Kemudian mengembangkan bahan ajar model pendidikan karakter di Sekolah Dasar Parangtambung 2 Kota Makassar. Hasil dari penelitian ini yaitu model Pendidikan karakter dapat menjadi sarana untuk mencegah kejahatan dan demoralisasi pada anak di SDN Parangtambung 2 Kota Makassar, Indonesia.